Performance evaluation of municipal services with fuzzy multi-criteria decision making approaches: a case study from Turkey - Ozdogan, Seyma; Yildizbasi, Abdullah; Rouyendegh, Babak Daneshvar (SN applied sciences, 2020)
Performance evaluation is a multi-criteria decision making subject to assign effective municipal services. Municipalities are the organizations that see the common needs and services of a city or county, and the person in charge of the municipal administration is called the “mayor.” The biggest duty of the mayor is to create an atmosphere of peace for the residents of the town where it is located, to respond to the needs of the town and the public and to conduct appropriate meetings. Mayors must meet all the requirements to make his/her town better and more functional. However, it is also not possible and takes a long time to meet all the needs of the people at the perfect level because of limited sources that municipalities have. Therefore, mayors should prioritize the tasks that can satisfy the public the most among the services they offer to the public. In this study, the fuzzy analytic hierarchy process and fuzzy technique for order preference by similarity to ideal solution methods, which are widely used in the literature, were used for the prioritization of the municipal services. This study is expected to shed light on mayors with limited resources to increase public satisfaction in the short term.